The research was carried out to isolate and characterize of bioactive proteins from plant parts of Benincasa hispida (Thunb.) Cogn and to analyse of the toxicity and cytotoxicity of the proteins. The proteins were extracted with phosphate buffer saline, then they were precipitated using 80% saturated ammonium sulphate, continued with the dialysis using pH 7 phosphate buffer. The dialysate was fractionated through gel filtration chromatography and characterized using SDS-PAGE. The toxicity of th - CHURIYAH CHURIYAH; LATIFAH KOSIM DARUSMAN (HAYATI Journal of Biosciences, 2009)
The research was carried out to isolate and characterize of bioactive proteins from plant parts of Benincasa hispida (Thunb.) Cogn and to analyse of the toxicity and cytotoxicity of the proteins. The proteins were extracted with phosphate buffer saline, then they were precipitated using 80% saturated ammonium sulphate, continued with the dialysis  using pH 7 phosphate buffer. The dialysate was fractionated through gel filtration chromatography and characterized using SDS-PAGE. The toxicity of the proteins was analyzed through brine shrimp lethality test (BSLT), followed with cytotoxicity test using HeLa and K-562 cancer cell lines. Three bioactive protein fractions were isolated from the fruits, the seeds and roots. The lowest yield of proteins was 0.021% from the fruit, then 0.051% from the seed, while the highest was 0.54% from the root. All proteins were toxic on BSLT with LC50 within the range of 24-39 µg. Characterization of proteins using SDS-PAGE indicated the molecular mass of those proteins were approximately 17-29 kDa. The cytotoxicity test of the root protein showed that the protein could inhibit proliferation of HeLa cell up to 28.50% and K-562 cell up to 36.60% compared to that  of non treated cell.                   Key words: Benincasa hispida (Thunb.) Cogn, bioactive protein, cytotoxicity